Mutation Landscape and Error Correction in Q-DNA : Correlated Errors, Structural Redundancy, and Topological Self-Correction in a Tetra-Stranded Hereditary Polymer - Barack Ndenga (Publisher, 2025)
Error accumulation is a fundamental limitation of any hereditary polymer. Canonical duplex DNA mitigates replication noise through enzymatic proofreading and repair, but remains vulnerable to independent, local errors. In this work, I develop a theoretical framework for mutation, noise, and error correction in Q-DNA, defined as a canonical tetra-stranded hereditary polymer. I show that tetra-strand coupling generically produces correlated error patterns and enables structural and topological error-correction mechanisms unavailable to duplex systems. I derive theoretical error rates under correlated noise, analyze majority- and consensus-based correction schemes, and identify structural motifs capable of intrinsic self-correction. These results position Q-DNA as a system in which error correction may be partially embedded in geometry and topology rather than relying exclusively on enzymatic machinery.
Replication noise and mutation accumulation impose fundamental limits on the viability of any hereditary polymer. In canonical duplex DNA, replication errors are often modeled as largely independent, local events, and error suppression relies primarily on enzymatic proofreading and repair. However, this architecture provides limited intrinsic redundancy and places strong constraints on genome length and evolvability. In this work, I develop a theoretical framework for mutation, noise, and error correction in Q-DNA, defined as a canonical tetra-stranded hereditary polymer. I show that tetra-strand coupling generically produces correlated error patterns and enables structural and topological error-correction mechanisms that are unavailable to duplex genetic systems. By explicitly modeling multi-strand correlated noise, I derive theoretical expressions for effective error rates under majority- and consensus-based correction schemes. I demonstrate that structural redundancy embedded in tetra-stranded geometry can suppress effective mutation rates from linear scaling to higher-order scaling, without requiring expanded chemical alphabets or fully enzyme-dependent repair. In addition, I identify classes of self-correcting motifs, in which topological constraints energetically exclude inconsistent mutation patterns and drive spontaneous error relaxation. Finally, I formulate falsifiable predictions regarding correlated mutation signatures, forbidden error configurations, and enhanced tolerance to raw replication noise. By treating error correction as an intrinsic physical property of a hereditary polymer rather than solely a biochemical process, this work establishes mutation control as a decisive criterion for evaluating Q-DNA as a viable alternative genetic system and situates tetra-stranded heredity within a rigorous framework of information theory, biophysics, and theoretical biology.